2023
DOI: 10.3390/molecules28041861
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydroxytyrosol in Endothelial Functioning: A Comprehensive Review

Abstract: Pharmacologists have been emphasizing and applying plant and herbal-based treatments in vascular diseases for decades now. Olives, for example, are a traditional symbol of the Mediterranean diet. Hydroxytyrosol is an olive-derived compound known for its antioxidant and cardioprotective effects. Acknowledging the merit of antioxidants in maintaining endothelial function warrants the application of hydroxytyrosol in endothelial dysfunction salvage and recovery. Endothelial dysfunction (ED) is an impairment of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 187 publications
0
6
0
1
Order By: Relevance
“…Numerous studies have shown the ability of HT to significantly reduce the buildup of ROS in diverse cellular contexts [ 7 ]. For example, it has been shown in many studies that HT has the ability to shield vascular endothelial cells from the harmful impacts of hydrogen peroxide [ 8 , 9 ]. Additionally, HT has also been found to provide protection to mammary cells [ 10 ] and human peripheral blood mononuclear cells (PBMCs) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown the ability of HT to significantly reduce the buildup of ROS in diverse cellular contexts [ 7 ]. For example, it has been shown in many studies that HT has the ability to shield vascular endothelial cells from the harmful impacts of hydrogen peroxide [ 8 , 9 ]. Additionally, HT has also been found to provide protection to mammary cells [ 10 ] and human peripheral blood mononuclear cells (PBMCs) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Olive leaves’ biological compounds yield cardiovascular-protective properties [ 19 ]. Not only do numerous studies confirm that olive leaves are able to decline blood pressure, improve blood flow in the coronary arteries [ 20 , 21 ], regulate arrhythmia, and prevent intestinal smooth muscle spasms [ 22 ], but their antimicrobial potential against bacteria, fungi, and mycoplasma has also been highlighted [ 23 , 24 , 25 , 26 , 27 ]. Like olive oil, the therapeutic benefits of O. europaea L. folium have been credited to low-molecular-weight polyphenols such as oleuropein (up to 60–90 mg/g dry leaf weight), hydroxytyrosol, tyrosol, and vitamin E isomers of tocopherol, elenolic acid derivatives, caffeic acid, p -coumaric acid, and vanillic acid, as well as flavonoids—luteolin, diosmetin, rutin, luteolin-7-glucoside, apigenin-7-glucoside, and diosmetin-7-glucoside [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…HT is a small molecule, so the ratio of its bioactivity to weight is greater than OLE’s. HT exerts strong antioxidant activity and is strongly associated with beneficial effects in various human diseases [ 17 ], manifesting anti-tumor [ 18 , 19 ], cardioprotective [ 20 , 21 ], and neuroprotective effects [ 22 , 23 ]. The strong protective activity of HT is also displayed against heavy metal-caused damage.…”
Section: Introductionmentioning
confidence: 99%